Divine visitations and hospitality to strangers in Luke-Acts: an interpretation of the Malta episode in Acts 28:1-10 - Jipp, Joshua W. (Supplements to Novum Testamentum, 2013)
This study presents a coherent interpretation of the Malta episode by arguing that Acts 28:1-10 narrates a theoxeny, that is, an account of unknowing hospitality to a god which results in the establishment of a fictive kinship relationship between the Maltese barbarians and Paul and his God. In light of the connection between hospitality and piety to the gods in the ancient Mediterranean, Luke ends his second volume in this manner to portray Gentile hospitality as the appropriate response to Paul's message of God's salvation - a response that portrays them as hospitable exemplars within the Lukan narrative and contrasts them with the Roman Jews who reject Paul and his message